Alternation preferences affect focus marking in German and English differently - Schauffler, Nadja (Frontiers in Psychology, 2023)
This study investigates the interplay between alternation preferences and corrective focus marking in the production of German and English speakers. Both languages prefer an alternation of strong and weak, and both use pitch accenting to indicate focus structure. The objective of the study is to determine whether the preference for rhythmic alternation can account for variations in the prosodic marking of focus. Contrary to previous claims, the results obtained from three production experiments indicate that rhythmic adjustment strategies do occur during focus marking. However, despite the similarities between the two languages, they employ different strategies when alternation and focus marking work in opposite directions. German speakers often employ a melodic alternation of high and low by realizing the first of two adjacent focus accents with a rising pitch accent (L*H), while English speakers frequently omit the first focus accent in clash contexts. This finding is further supported by a second experiment that investigates pitch accent clashes in rhythm rule contexts under various focus environments. The findings suggest that the preference for alternation can influence the prosodic marking of focus and contributes to variation in the realization of information-structure categories.